Заметки к теории струн: топологическое моделирование квантовой реальности - Бугаёв, А.Ф. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
Do the basic assumptions (axioms) about quantum reality (CD), from which the
law changes the properties of the CD and its structure, which reproduces the structure
of observable reality.